Takhrij and Syarah Hadith of Agrotechnology: Benefits of Fruits and Olive Oil - Muhammad Fauzan; Esty Puri Utami; Wahyudin Darmalaksana (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith of the Prophet Muhammad ï·º regarding fruit and olive oil. This research method is a qualitative type through literature study and field studies with the takhrij and sharah hadith approaches. Results and discussion of this research olive is a plant endowed by Allah which has many benefits. The conclusion of this study is that the takhrij and syarah of agrotechnology hadith regarding fruit and olive oil are proven to have better quality than vegetable oils and other animal oils because they do not have side effects that can cause disease.